Minimum cost upgrade of phasor measurement unit networks for synchrophasor availability. (15th October 2013) - Huang, Jianzhuang; Wu, N. Eva; Odgaard, P. F.; Aubrun, C.; Majanne, Y.
SUMMARY This paper considers the problem of placing additional phasor measurement units (PMUs) and communication links into a PMU network in a power system. The objective is for the synchrophasors (PMU outputs) across the power system to meet a prescribed availability profile with fewest new PMUs and links among them. Achieving a required synchrophasor availability profile is critical in supporting wide area monitoring, protection, and control in a power system. In our recently reported work, synchrophasor availability is solved from a controlled Markov chain where binary variables indicating placement decisions are embedded as stationary control variables. In this paper, the assumption that communication links are always available wherever needed is removed. Random interruptions in PMU communications are modeled in such a way that the reformulated placement problem remains Boolean‐convex, and the computational complexity with respect to the number of buses remains O(n2). The solution to placement of PMUs and communication links into the Institute of Electrical and Electronics Engineers (IEEE) 118‐bus test system is presented. Copyright © 2013 John Wiley & Sons, Ltd.